STRATEGY INCREASES SHARE PRICES IN TECHNOLOGY SECTOR COMPANIES - Evina Wijaya; Khairudin (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
The offer of shares is used by market participants to calculate the stock price, which is the price of a share in the capital market at a certain time. The technology sector saw a decline of almost half by 42.61% in one year in 2022, a phenomenon that caught the author's attention in reviewing the financial performance of the industry. This research uses Return on Equity, Current Ratio, Debt to Asset, and Earnings Per Share as a measure of stock price to determine the impact on financial performance. This research uses a quantitative approach utilizing secondary data in 2020–2022 and purposive sampling to obtain sample data. The findings of this research are: (1) profitability has a negative and insignificant effect on stock prices; (2) liquidity has a negative and insignificant effect on stock prices; (3) solvency has a positive and significant effect on stock prices; (4) Market value has a positive and significant effect on stock prices. The suggestion in this research is for all parties (management, investors, potential investors) to pay more attention to profitability and liquidity to be able to predict the value of a company and the next researcher, to add samples and other variables such as ROA, DER and PER, which are able to explain the effect of financial performance on stock prices.